Sensory and Flavor Characteristics of Tomato Juice from Garden Gem and Roma Tomatoes with Comparison to Commercial Tomato Juice. Issue 1 (14th November 2017) - Zhu, Yaozhou; Sims, Charles A.; Klee, Harry J.; Sarnoski, Paul J.
Abstract : Abstract: The objective of this study was to characterize the flavor of a premium Florida tomato variety that has significant potential for producing a high quality processed juice product. A high‐quality Florida plum tomato variety (Garden Gem), and a typical grocery‐store plum tomato variety (Roma) were thermally processed into tomato juices without any additives. The 2 pilot products and a popular commercially available tomato juice (low sodium with sugar and flavor added) were compared using sensory evaluation and instrumental analysis. Flavor compounds in these products were identified using dynamic headspace purge and trap‐gas chromatography‐mass spectrometry (PT‐GC‐MS) by MS library match and retention index and were semi‐quantitated using internal standards. Color, uniformity, overall liking, tomato flavor, sweetness and texture were rated using a hedonic scale. Analysis of variance, correlation and principal component analysis were used to analyze both sensory and flavor data. Among the 3 products, Garden Gem juice was rated significantly ( P < 0.05) higher for overall liking, tomato flavor, and sweetness by the 119 consumer panelists in both seasons. Garden Gem juice was found to contain higher levels of 3 sweet/fruity related aroma compounds: 6‐methyl‐5‐hepten‐2‐one, linalool, and β‐ionone. The commercial tomato juice contained a high level of the Maillard reaction‐related notes furfural, dimethyl sulfide, and the least amount of green‐related notes (hexanal, E‐2‐hexenal and Z‐2‐heptenal). The flavor profile of the Roma tomato juice was similar to Garden Gem juice except it contained substantially lower amounts of hexanal and 2‐isobutylthiazole. The compound β‐ionone (fruity note) was not detected in either the commercial or Roma juice. Practical Application: This proof of concept study demonstrates that high flavor quality tomatoes can be used to create better tasting processed tomato products. The study also demonstrates how sensory preference can confer a potential market advantage over existing commercial products. The Garden Gem variety has potential to add desirable flavor attributes to processed tomato products. This research may also provide insights for product developers to which flavor volatiles best reflect sensory observations for different aspects of tomato flavor.